PERSEPSI IBU HAMIL TENTANG ANEMIA DI UPTD PUSKEMAS KUTA SELATAN - Kusuma, Arya Leonyta; Lubis, Dinar Saurmauli; Ekawati, Ni Komang; Kartika Sari, Komang Ayu (ARCHIVE OF COMMUNITY HEALTH, 2025)
Maternal mortality rate which is an indicator of success in maternal health efforts. In Bali Province, the maternal mortality rate in 2021 is 189.65 per 100,000 live births, of which 7.2% are caused by bleeding. The problem of anemia in pregnant women is also found in the South Kuta Health Center and in 2021 there will be 22.63% cases of anemia in pregnant women. The aim of the study was to find out how pregnant women perceive anemia in the UPTD Puskesmas South Kuta work area. This research is a descriptive qualitative research. Selection of informants using a purposive technique with a total of 10 informants. Data was collected using the in-depth interview method. Then analyzed using thematic analysis techniques. Data validation uses source triangulation techniques and peer debriefing techniques. The results showed that pregnant women perceive anemia as a health situation that can affect the health of their pregnancy. Most pregnant women already know about the impact and risks as well as what preventive measures can be taken to prevent anemia. The perception of pregnant women about anemia is influenced by many things, such as the economy, family support, local culture and beliefs, as well as information obtained by pregnant women. Keywords: Perception, Pregnant Women, Anemia